Biological effects of dynamic shear stress in cardiovascular pathologies and devices - Girdhar, Gaurav (2008)
Altered and highly dynamic shear stress conditions have been implicated in endothelial dysfunction leading to cardiovascular disease, and in thromboembolic complications in prosthetic cardiovascular devices. In addition to vascular damage, the pathological flow patterns characterizing cardiovascular pathologies and blood flow in prosthetic devices induce shear activation and damage to blood constituents. Investigation of the specific and accentuated effects of such flow-induced perturbations on individual cell-types in vitro is critical for the optimization of device design, whereby specific design modifications can be made to minimize such perturbations. Such effects are also critical in understanding the development of cardiovascular disease. This review addresses limitations to replicate such dynamic flow conditions in vitro and also introduces the idea of modified in vitro devices, one of which is developed in the authors' laboratory, with dynamic capabilities to investigate the aforementioned effects in greater detail.